COMMUNION: towards a cooperative strategy for high-performance memory management - Midorikawa, Edson Toshimi; Sato, Liria Matsumoto (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1997: Anais do IX Simpósio Brasileiro de Arquitetura de Computadores e Processamento de Alto DesempenhoDO - 10.5753/sbac-pad.1997.22645, 1997)
The memory system is the most critical component of modern high-performance computer systems, because of its growing inability to keep up with the processor requests. Technological trends have produced a large and growing gap between CPU speeds and DRAM speeds. Many researches have focused this memory system problem, including program optimizing techniques, data locality enhancement, hardware and software prefetching, decoupled architectures, mutithreading, speculative loads and execution. These techniques have achieved a relative suceess, but they focus only one component in the hardware or software systems. We present here a new strategy for memory management in high-performance computer systems, named COMMUNION. The basic idea behind this strategy is cooperation. We introduce some possibilities of interaction among system programs that are responsible to generate and execute application programs. So, we investigate two specific interactions: between the compiler and the operating system, and among the compiling system components. The experimental results show that it's possible to achieve improvements of about 10 times in execution time, and about 5 times in memory demand. In the interaction between compiler and operating system, named Compiler-Aided Page Replacement (CAPR), we achieved a reduction of about 10% in the space-time product, with an increase of only 0.5% in the total execution time. All these results show that it's possible to manage main memory with better efficiency than what is provided by current systems.